El reconocimiento del matrimonio igualitario y su influencia al acceder a la adopción homoparental. - Salgado Rohoden, Ernesto Rafael (2023)
This research work is good enough to put into consideration of the readers, the indisputable problem that entails the ignorance of the rights of people belonging to LGBTIQ+ groups by the Ecuadorian state; This state obligation has been sought to be resolved by means of a Constitutional Court ruling in the exercise of the Concrete Control of Constitutionality, therefore, the legitimacy of the aforementioned instrument will be analyzed, as well as what it has caused in the people who have sought the exercise thereof. With this, it is intended to spread that these needs have a further purpose that is not limited to the subjective desires or claims of people, but rather, to understand that this constitutes a legitimate obligation that corresponds to the state as the main guarantor of rights Finally, explain what consequences people have who are constitutionally excluded from possibilities that other couples can access without much difficulty.